Education–work transition: skill gaps in the construction industry - Bhattarai, Prakash C.; Parajuli, Mahesh Nath; Gautam, Suresh; Paudel, Prakash Kumar; Bhurtel, Anup; Sharma, Amrita (Frontiers in Built Environment, 2025)
This study aimed to assess the skills gap between competency evaluations by employers and the self-perceived competencies of employees within the engineering sector of the construction industry. We also examined the foundational subject matter knowledge of graduate employees and their likelihood of acquiring such knowledge based on different variables like gender, ethnicity, infrastructure quality, and the quality of on-the-job training (OJT). Accordingly, we conducted a cross-sectional survey using a self-administered questionnaire, which was completed by 59 employers and 222 recent graduates. From the perspective of the employers, the findings indicate that the majority of graduates exhibit inadequate proficiency in soft skills, professional competencies, common technical skills, and trade-specific abilities. Furthermore, the graduates demonstrated limited subject matter knowledge, with an average score of only 50.98% on a basic knowledge assessment. The analysis also revealed that graduates with access to high-quality institutional infrastructure and OJT opportunities performed nearly twice as well on the foundational knowledge test compared to those with poorer-quality experiences in these areas. These results highlight the urgent need to revise the technical and vocational education and training (TVET) curriculum as well as strengthen collaborations between training institutions and industry stakeholders to ensure that graduate competencies are aligned with the labor market demands.